2017
DOI: 10.12968/pnur.2017.28.9.386
|View full text |Cite
|
Sign up to set email alerts
|

Barriers between offenders and primary health care after release from prison: a case study

Abstract: A lack of support is just one of the problems facing former prisoners when it comes to obtaining primary health care after release. Claire Carswell and colleagues use one specific case study to highlight the many general difficulties that threaten former inmates' wellbeing Post-release prisoners in the United Kingdom experience health inequalities, poor continuity of care during the transition from prison to the community, and high morbidity and mortality rates. Primary health care is a necessary support for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…There are likely to be some important differences among different populations experiencing incarceration who are eligible for PrEP, and characterizing these nuances in clinical care will be important to fully understanding what is required to encourage PrEP uptake and engagement in care among criminal justice–involved individuals. Finally, this population experiences many challenges in being linked to care while also experiencing extremely high risk for HIV acquisition [ 10 , 17 , 58 , 59 ]. Successful implementation of PrEP care within the criminal justice system and linking criminal justice–involved individuals to PrEP care in the community has the potential to significantly reduce the spread of HIV both within the criminal justice setting and the broader community, and is an important step to ending the HIV epidemic in the United States [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are likely to be some important differences among different populations experiencing incarceration who are eligible for PrEP, and characterizing these nuances in clinical care will be important to fully understanding what is required to encourage PrEP uptake and engagement in care among criminal justice–involved individuals. Finally, this population experiences many challenges in being linked to care while also experiencing extremely high risk for HIV acquisition [ 10 , 17 , 58 , 59 ]. Successful implementation of PrEP care within the criminal justice system and linking criminal justice–involved individuals to PrEP care in the community has the potential to significantly reduce the spread of HIV both within the criminal justice setting and the broader community, and is an important step to ending the HIV epidemic in the United States [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of continuity of care was also highlighted by the United Nations in the Mandela Rules (rule 24.2), which emphasised that prison health care services should be organised in close connection to the general health care system and in such a way that it ensures continuity of care and treatment, including for HIV, other infectious diseases, and drug dependency (UN Office on Drugs and Crime, 2015). Research consistently emphasised both the importance and ongoing challenges of continuity of care during the transition from prisons to the community (Kouyoumdjian, Wiwcharuk and Green 2015;Carswell et al, 2017). For instance, an Australian medical record study showed that for female prisoners the transfer of health information from prison to community care was better in situations where a formal programme of information exchange existed, suggesting that outside such formal programmes transfer of health information is limited (Abbott et al, 2017a).…”
Section: Primary Care During and After Detention And Continuity Of Ca...mentioning
confidence: 99%
“…Individuals in the criminal justice system (CJS) have a high prevalence of physical and mental health-care needs, have lower psychological well-being 2 and experience significant problems in accessing health and social care services. 3 Services for those with multimorbidities who are under community supervision often appear fragmented. 4 Key barriers to access to health-care services include general practice registration, long waiting times for appointments and a perception of not being supported by services to make contact, such as probation.…”
Section: Scientific Backgroundmentioning
confidence: 99%